(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
The traditional financial theories such as modern portfolio theory, efficient market hypothesis dominated the financial world for almost two decades. The emerging field of behavioral finance investigated the sociological and psychological issues and their impact on the financial decision making of individual and institutional investors. In this paper, we highlighted some of the prevalent common behavioral biases among the investors and their impact on individual investors, institutional investors, market and regulators. A checklist of behavioral biases must be prepared by the investors before making an investment decision in the stock market.